Efektivitas Metode Lamaze Terhadap Tingkat Nyeri Pada Ibu Bersalin: Effectiveness of the Lamaze Method on the Level of Pain in Nursing Mothers - Ihda Nabilah Rumaitsa; Evi Yunita Nugrahini; Dwi Purwanti; Siti Mar’atus Sholikah (Gema Bidan Indonesia, 2022)
Labor pain is defined as a condition that feels unpleasant and very subjective because each mother’s pain treshold is different either scale or level. If not controlled properly, it will have an impact on the health of the mother, baby and delivery process. Pain control due to contractions needs to be done, among others, by the Lamaze method. Objective: To find out the effectiveness of the Lamaze method against the pain level of maternity mothers. Method:This research is a Literature Review by reviewing customized articles. Article searches were conducted in 4 databases (Proquest, ResearchGate, Semantic Scholar and Google Scholar) using Boolean Operators with article selection using PRISMA Flowchart as well as article quality assesment using JBI Critical Appraisal. The results found 17 articles that met the inclusion. Results: After reviewing 17 articles, 10 of them stated that the Lamaze method proved effective against reducing the level of labor pain. In addition to pain, 5 article stated that the Lamaze method affects anxiety, 4 articles stated that this method affects the duration of labor and 6 articles state that this method is able to improve a good and healthy labor outcomes. Conclusion: The results of the study based on a review of 17 articles obtained, concluded that the Lamaze method proved effective in reducing pain levels in maternity mothers. In addition, this method also affects the level of anxiety, the duration of labor and labor outcomes (both maternal/neonatal outcomes). Implications: To add to the Literature Review related to the management of labor pain in a non pharmacological manner using the Lamaze method.